PENENTUAN ARAH KIBLAT MENGGUNAKAN RUBU' MUJAYYAB : STUDY PENELITIAN DI MASJID AN-NUR PARE - Ali, Sapri; Muhammad Ansori (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
A variety of classical and modern tools, such as sticks, theodolites, and GPS, are used in determining the direction of the Qibla, which causes differences of opinion among astronomers. Modern tools such as compasses further increase the accuracy of Qibla direction by utilizing magnetic needle technology. The author is interested in discussing rubu' mujayyab, a classic tool that has advantages and disadvantages but is still used by astronomers in Islamic boarding schools. In this research, the issue discussed is what is the level of accuracy in determining the Qibla direction using rubu' mujayyab? What are the advantages and disadvantages of determining Qibla direction using rubu' mujayyab? The type of research used by this author is classified as qualitative, which aims to better understand Rubu Mujayyad where the primary data is data obtained directly from observations, the book Durussul Falakiyyah, and the secondary data is all documents in the form of books, writings, journals, papers related to the object. study. The findings resulting from this research are that when the practice of measuring the Qibla is not the same, there is a difference of around 0˚ 8′ 52.42ʺ which if converted into meters from the distance from east to west are both 9 meters results in a difference of around 0.03 meters. According to the author, this is still within reasonable limits or the allowable deviation category. Maybe this is due in part to the advantages and disadvantages of each of these two tools. The advantage contained in rubu' mujayyab is that it is more accurate because it relies on direct sunlight. Meanwhile, the disadvantage of rubu' mujayyab is that the data in rubu' mujayyab is limited to degree data only so it requires accuracy from the person doing the calculations, only astronomers can do it, it cannot be used in cloudy conditions, and so on.